Natural (−)‐Vasicine as a Novel Source of Optically Pure 1‐Benzylpyrrolidin‐3‐ol. Issue 5 (17th May 2013) - Aga, Mushtaq A.; Kumar, Brijesh; Rouf, Abdul; Shah, Bhahwal A.; Andotra, Samar S.; Taneja, Subhash C.
Abstract A facile and scalable methodology for the preparation of optically active (3S)‐1‐benzylpyrrolidin‐3‐ol (3), an important drug precursor, is reported. Starting from the naturally occurring alkaloid (−)‐vasicine (1), a major alkaloid of the plant Adhatoda vasica, 3 was obtained in 84% overall yield (Scheme 3).